Intergenerational Relationship Quality, Gender and Grandparent Involvement - Barnett, Melissa A. (2010)
This prospective, intergenerational study (N = 181) considered how parent (G1, generation 1)–child (G2, generation 2) relationship quality during adolescence and adulthood is associated with G1’s level of involvement with their 3–4 year-old grandchildren (G3, generation 3). Path model analyses indicated different patterns of results for the involvement of grandmothers and grandfathers with the children of their G2 sons and daughters. Current parent-reported G1-G2 relationship quality was positively associated with G2 report of G1 involvement with G3, especially for G2 daughters. The relations among confounding variables, including geographic distance, socioeconomic status, and grandparent marital status and grandparent involvement with grandchildren were considered. Results highlight the roles of intergenerational relationship quality and gender configuration of the G1-G2 dyad in shaping grandparent involvement with grandchildren.